The Societal Integration of Immigrants in Germany - Michael Fertig (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2004)
This paper investigates whether and to what extent immigrants in Germany are integrated into German society by utilizing a variety of qualitative information and subjective data collected in the 1999 wave of the German Socio- Economic Panel (GSOEP).To this end, leisure-time activities and attitudes of native Germans, ethnic Germans and foreign immigrants of different generations are compared. The empirical results suggest that conditional on observable characteristics the activities and attitudes of foreign immigrants from both generations differ much more from those of native Germans than the activities/ attitudes of ethnic Germans. Furthermore, the attitudes of second-generation immigrants tend to be characterized by a larger degree of fatalism, pessimism and self-doubt than those of all other groups, although their activities and participation in societal life resemble more those of native Germans than those of their parents generation.
Keywords: J15; J61; 330; Subjective data; first- and second-generation immigrants; ethnic Germans; Migranten; Soziale Integration; Aussiedler; Generationenbeziehungen; Schätzung; Deutschland